Semiotic Analysis of the Film Dirty Vote in the 2024 Election - Amin, Amin; Habib, Mohd. Nadzrizal; Putri, Melani Andika; Poetri, Maharanny Setiawan (International Journal of Education, Information Technology, and Others, 2024)
This research analyzes the documentary “Dirty Vote” using Ferdinand de Saussure's semiotic analysis to identify and interpret the signs and symbols used in the film. The film, which was released ahead of the 2024 General Election, raises the issue of fraud in Indonesia's electoral process. The semiotic analysis shows that the signs in the film represent complex political strategies and manipulations, including the use of the chess game symbol to illustrate careful planning and the term "pork barrel politics" to indicate the use of public funds for private interests. In addition, the “4-finger salute” symbol indicates the merging of certain political forces. The film "Dirty Vote" succeeded in raising public awareness of the importance of transparency and fairness in the electoral process, as well as motivating people's active participation in election monitoring.